Knowledge, attitude and practices related to COVID-19 among young Lebanese population - Samer Sakr; Ali Ghaddar; Imtithal Sheet; Ali H. Eid; Bassam Hamam (BMC, 2021)
Abstract Background As the world faces the most serious and widespread pandemic in recent history, claiming nearly 1,945,610 lives and infecting over 90 million individuals up to January 13, 2021, controlling the spread of COVID-19 is still limited to efforts done by the general population implementing rules and restrictions passed by world governments and organizations. As we wait for the approved vaccines to become widely distributed, the best approach to fighting the spread of this disease is mostly preventative depending largely on individuals' compliance. This study aimed to determine the knowledge, attitude and practices (KAP) towards COVID-19 in Lebanon. Methods A descriptive analysis was performed to describe the outcome measures of knowledge, attitudes and practices towards COVID-19 on a convenience sample from the Lebanese population in relation to socio-demographic characteristics and level of concern towards COVID-19. One thousand eight hundred sixty-one participants filled in an online survey (response rate: 18.5%) distributed by social media to social networks of the research team members. Results Participants were mainly young (49.4% between 18 and 24 years) and males (73.7%). Participants showed an overall appropriate knowledge of COVID-19 (67.1%) and positive attitude (around 90% were optimistic about treatment and vaccination) and had good preventive practices towards COVID-19 (around 75% washed hands and avoided public places). Knowledge and practices correlated positively with marriage, age, education, working in a healthcare field and with the level of concern about getting COVID-19. Conclusions This study found good overall levels of KAP among the studied Lebanese population. This can help in controlling the spread of COVID-19 if individuals were forced to adhere to social distancing and appropriate preventative practices.